APPLICATION OF THE RECITATION METHOD IN LEARNING BUILD A FLAT SIDE ROOM FOR CLASS VIII STUDENTS OF MTsS KEUTAPANG DUA ACEH BESAR - Zulfandi Zulfandi (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2022)
One of the causes of the low student mathematics learning outcomes is the inappropriate use of the learning methods used in class. One solution to overcome this problem can be applied to a method that can improve student learning outcomes. This study aims to determine the increase in student learning outcomes and mastery of the application of the use of the recitation method in class VIII MTsS Keutapang Dua Aceh Besar. This type of research is experimental research. The population of all students in class VIII MTsS Keutapang Dua Aceh Besar totaling 59 students, while the provisions for taking samples using random sampling, namely the technique of determining samples randomly based on a lottery so that a sample of students in class VIII-A as the experimental class and VIII-B as the control class is obtained. Data collection techniques are through pretest and posttest, data analysis techniques using t-test (t-scroe) and the percentage of completeness of student learning outcomes. The results showed that the comparison of tcount ttable values, namely 2.44 1.68 which indicated that student achievement taught by the recitation method was better than student achievement taught without the recitation method on flat sided geometric material with learning mastery reaching 75%.Keywords: Recitation Method, Build Space, Flat Side